Pengaruh Motivasi, Komunikasi dan Disiplin Kerja terhadap Kinerja Karyawan - Farraquena Chandra Dwirizkalia; Surahman Pujianto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to analyze and determine the influence of motivation, communication, and work discipline on the performance of PT. XYZ. The population used in this study were employees of PT. XYZ has 169 employees. The sampling technique used is a purposive sample where the sampling technique with certain considerations that is sampled is 108 employees of PT. XYZ. Data retrieval techniques through the dissemination of questionnaires using a Likert scale. The data is then analyzed using statistical data processing. Based on the results of hypothesis test data analysis in this study, it shows that motivation has a significant effect on employee performance, communication has a significant effect on employee performance, and work discipline has a significant effect on employee performance.